PELATIHAN PLIOMETRIK ALTERNATE LEG BOUND DAN DOUBLE LEG BOUND MENINGKATKAN DAYA LEDAK OTOT TUNGKAI PADA SISWA PUTRA KELAS VII SMP NEGERI 3 SUKAWATI TAHUN PELAJARAN 2012/2013 - Tri Widhiyanti, Komang Ayu; Tirtayasa, Ketut; Pangkahila, Alex (Sport and Fitness Journal; Volume 1, No.2, 2013)
This study was conducted to know the improvement the explosive power of leg muscle. It was done through 5 set 12 repetitions during 6 weeks in the field of SMP Negeri 3 Sukawati started from 4 p.m. until 6 p.m. There were 3 groups applied in this study such as group 1 (control group) that was instructed to kick a ball, group 2 (plyometric training of alternate leg bound), and group 3 (plyometric training of double leg bound). The sample was 14 male students who were in the seventh grade class of SMP Negeri 3 Sukawati in the academic year 2012/2013. The data was gained by doing the movement of alternate leg bound and double leg bound that each movement was done three times before and after the training. The hypothesis was examined by using independent t-test with the result 0.05 (p<0.05). Based on the different result of analysis test in each group, the gain score of the group 2 with the group 1 about 0,51 that shows the significant differences p = 0,00, the gain score of the group 2 with the group 3 about 0,31 that shows the significant differences p = 0,00, the gain score of the group 3 with the group 1 about 0,20 that shows the significant differences p = 0,00. Thus, alternate leg bound plyometric training is more effective than double leg bound. It is expected that the coach and the gym teacher to apply alternate leg bound plyometric training as an alternative to improve the explosive power of leg muscle.
Keywords: alternate leg bound plyometric training, double leg bound plyometric training, the explosive power of leg muscle.